Квазіпотрійна система Tl2Se–TlInSe2–Tl4P2Se6 - Барчій Ігор; Barchii Ihor; Товт Валерія; Valeriya Tovt; П'ясецкі Міхал; Michal Piasecki; Федорчук Анатолій; Anatolii Fedorchuk; Погодін Артем; Pogodin Artem; Філеп Михайло; Filep Mykhailo; et al. (My University, 2019)
Резюме. Вперше методами фізико-хімічного аналізу (ДТА, РФА, МСА) досліджено фазові рівноваги в квазіпотрійній системі Tl2Se–TlInSe2–Tl4P2Se6 , побудовано просторову діаграму стану, проекцію поверхні ліквідусу на концентраційний трикутник. Встановлено, що система характеризується евтектичним типом взаємодії з утворенням граничних твердих розчинів на основі вихідних компонентів. З кристалохімічних позицій розглянуто закономірності зміни типу хімічного зв’язку при переході від бінарного Tl2Se до тернарних сполук TlInSe2 , Tl4P2Se6 та механізму формування твердих розчинів.

Abstract. Complex chalcogenide compound are widely used as working elements for semiconductor optical technology, thermal generation, solar power. Special attention is paid to compounds of the M2P2Se6 type (M – Ag, Cu) which due to its layer crystal structure possess promising ferroelectric, thermoelectric and electro-optical properties. Heterovalent substitutions of cations 2М2+ ® 4M1+ in the composition of M2P2Se6 type compounds must leads to deformation of the crystal structure, changing in the value of the dipole moment and, accordingly, to change the electro-physical properties. The Tl2Se–In2Se3–“P2Se4” system characterized by the formation of intermediate complex compounds which melts congruently TlInSe2 (1023 К), Tl4P2Se6 (758 К), TlInP2Se6 (875 К) and TlIn5Se8 (melts incongruently L+In2Se3«TlIn5Se8 at 1029 К), In4(P2Se6)3 (formed by syntactic reaction at 880 К). Triangulation of the Tl2Se–In2Se3–“P2Se4” system was shown that then divided on secondary quasiternary systems, one of them is Tl2Se–TlInSe2–Tl4P2Se6. Phase equilibria in the Tl2Se – TlInSe2 – Tl4P2Se6 quasiternary system were studied using classical methods of physicochemical analysis DTA (chromel-alumel thermocouple, with an accuracy of ±5 K), XRD (DRON-3-13 diffractometer, Cu Ka radiation, Ni filter, Guinier Huber G670 diffractometer, CuKα1 radiation), MSA (metallographic microscope Lomo Metam R1) in combination with the simplex method of mathematical modeling of phase equilibria in multi-component systems. Crystal structure calculation was carried out with program WinCSD. Investigation of physical-chemical interaction allowed to constructed perspective view of phase state diagram and liquidus surface projection of the Tl2Se–TlInSe2–Tl4P2Se6 ternary system. In the ternary system formed the boundary solid solution: a- on the basis of Tl2Se, b- on the basis of TlInSe2, g-, d-, e- on the basis of ltm-, mtm- and htm-Tl4P2Se6 (ltm, mtm, htm – low, middle and high temperature modification, respectively). The liquidus of the ternary system consists of primary crystallization areas: Tl2Se-е1-Е1-е2-Tl2Se (a phase), TlInSe2-е3-U2-U1-E1-TlInSe2 (b phase), m1-U1-E1-e2-m1 (g phase), m2-U2-U1-m1-m2 (d phase) and Tl4P2Se6-e5-U2-m2-Tl4P2Se6 (ε phase). The Tl2Se–TlInSe2–Tl4P2Se6 quasiternary system is characterized by the processes: monovariant eutectic L«htmTl4P2Se6+TlInSe2 (e5-U2, 776-693 К), monovariant eutectic L«Tl2Se+TlInSe2 (e1-Е1, 614-539 К), monovariant eutectic L«Tl2Sе+ltmTl4P2Se6 (e2-Е1, 610-539 К); monovariant peritectic L+mtmTl4P2Se6«ltmTl4P2Se6 (m1-U1, 640-620 К); monovariant peritectic L+htmTl4P2Se6« mtmTl4P2Se6 (m2-U2, 747-693 К); monovariant peritectic L+mtmTl4P2Se6«TlInSe2 (U2-U1, 693-620 К); monovariant peritectic L+ltmTl4P2Se6«TlInSe2 (U1-E1, 620-539 К). Lines of the monovariant equilibria are crossed in three point: U2 – invariant peritectic process L+htmTl4P2Se6«TlInSe2+mtmTl4P2Se6 (12 mol.% Tl2Se, 20 mol.% TlInSe2, 68 mol.% Tl4P2Se6, 693 К), U1 – invariant peritectic process L+mtmTl4P2Se6«TlInSe2+ltmTl4P2Se6 (38 mol.% Tl2Se, 9 mol.% TlInSe2, 53 mol.% Tl4P2Se6, 620 К), E1 – invariant eutectic process L « Tl2Se+TlInSe2+ltmTl4P2Se6 (47 mol.% Tl2Se, 7 mol.% TlInSe2, 46 mol.% Tl4P2Se6, 539 К). New complex compounds were not observed in the ternary system. Limited solid solutions on the basis of TlInSe2, Tl4P2Se6 initial compounds are not up to 5–8 mol%. Crystal-structure studies of Tl2Se, TlInSe2 and Tl4P2Se6 complex chalcogenides were carried out by a powder method, refinement of the structural parameters – by the Rietveld method. The lattice parameters are: Tl2Se – Р4/n, а=8,540; с=12,380 Å, TlInSe2 – I4/mcm, a=8.064, c=6.833 Å, Tl4P2Se6 – P121/c1, a=12.239, b=9.055, c=12.328 Å, b=98.83. Crystal-chemical analysis of the compounds showed that they are characterized by a mixed ion-covalent type of chemical bond. During the transition from the binary Tl2Se to TlInSe2 ternary compound the covalent component of the In–Se bond is enhanced, the opposite change is observed for Tl4P2Se6, an increase in the ion component of the Tl–Se bond. The study of the mechanisms of formation of solid solutions showed that with the reciprocal solubility of the TlInSe2, Tl4P2Se6 ternary compounds characterized by the formation of substitution structure, the dissolution of Tl2Se in ternary selenides follows the substitution and subtraction mechanism.
Tl2Se–TlInSe2–Tl4P2Se6 quasiternary system
Редакційна колегія: https://ucj.org.ua/index.php/journal/about/editorialTeam
Keywords: селенодифосфати; фазові рівноваги; діаграма стану; кристалічна структура; тверді розчини